Estimación de esfuerzo en desarrollo de software ágil: Estudio del estado actual en Bogotá (2020)
Context: Over the years, numerous studies have been developed related to estimating effort in agile software development, which allow us to understand the advances that have been made and the need for their use in companies. Objective: To know the perspective of entrepreneurs from different organizations in Bogotá that work in the sector or are related to the development of agile software and those who have had projects related to the subject. Method: For the elaboration of the article, a bibliographic research is carried out. Results: The data obtained are from 314 respondents in the city of Bogotá, the main findings are: 1) For companies it is extremely important with (34%) the adoption of an effort estimation methodology. 2) The most used estimation technique is the use case point with (43.31%). 3) The most used effort predictor is the Code Line (38.85%) and followed by this STORY POINT with (33.76%). 4) The agile methodology adopted in companies is SCRUM with (43.95%). 5) As the most determining factor to estimate the effort, the team experience with (53.50%) is considered. 6) In the percentage of error between estimate of projected effort and real effort (26.75%) of the respondents determine that this 5% -25% is underestimated. 7) Finally, as a difficulty in your company to estimate the effort of projects through agile software development, the respondents recognize (26.11%) that the resources are the greatest. Conclusions: The estimation of effort is relatively variable, for many companies this depends on the needs of each one, on the other hand, the use of agile methodology and estimation techniques varies in its use depending on the cross between them and how they are used. complement each other.